Improvement of Advancing Front Mesh method in triangle hole filling - Awang, Noorehan (2022)
Mesh-based or triangulated prototypes are widely used to represent objects in many modelling and computer-aided engineering applications. In certain cases, there is a possibility of missing points when scanning devices fail to enter certain regions; and those area captured as a hole in the scanning process. These holes need to be filled in order to develop an error-free triangulated prototype. The Advancing Front Mesh method is used to fill a triangle to overcome this problem. This method iteratively meshes a hole’s area by inserting new triangles and nodes at the hole’s boundary, then moves to the inside of the area until it is closed. However, problems occur when finding new points using this method. In this research, an improved Advancing Front Mesh method is proposed to solve the problem of filling holes when encounter three intersection problem for the triangular mesh. The first problem is that when a new generated point is unconnected to any active point, using the usual threshold circle. Thus the intersection point was calculated between the threshold circle to any line segment in a triangle in order to check for nearest active point. Secondly, the triangle created overlaps other triangles; the circumcircle surrounded all the starting points along with the new points was used to check for any extra active point. Then the magnitude was calculated between previous new point to the new active point to identify the correct points. Thirdly, when the new generated point is close to the hole’s boundary, the threshold radius have been enlarged in order to find the new point. Then the bisection point was calculated if there is no active point in the enlarged radius. The first validation is carried out using the interpolating surface of the test data with three familiar bivariate functions. Meanwhile, the second “visual similarity” validation is carried out using a questionnaire to compare the experimental outcome with the original figure. The results of this research contribute to the method of satisfying an object’s visualization and provides an enhanced method of AFM for filling a hole in triangular mesh.